Exploring the spectroscopy of vibrational levels in the 160 mass region - Majola, Siyabonga Ntokozo Thandoluhle (Department of Physics, 2016)
Vibrational levels are well known in atomic nuclei but despite many decades of research, some of their properties still remain elusive. In particular, low-lying rotational bands based on the first excited 0+ state, which are traditionally understood as β vibrational bands nevertheless show properties at odds with this interpretation, more especially in the transitional rare earth region with N~ 90 [Gar01]. An alternative is that they can be better be described as a "second vacuum", or coexisting minimum in the pairing degree of freedom [Sch11a]. In order to produce a complete and definitive microscopic picture of the so-called β and γ bands, an extensive systematic review is performed for nuclides in the 160 mass region, between N = 88 and 92 and Sm to Yb. The data are explained using a five dimensional collective Hamiltonian for quadrupole rotational and vibrational degrees of freedom [Li09, Nik09]. A good qualitative agreement is obtained between measured energies and electromagnetic transition rates across the entire A ~ 160 mass region. The implication of these findings on the interpretation the first excited 0+ states is there from discussed. In this study, the γ-ray spectroscopy of 156Dy and 157Dy are also revised. Three experiments with different reactions to produce 156Dy have been analyzed. The data were acquired using the 155Gd (α, 3n) 156Dy and 148Nd (12C, 4n) 156Dy and 124Sn (36S, 4n) 156Dy reactions at beam energies of 25, 65 and 165 MeV, respectively. The 155Gd (α, 3n) 156Dy experiment was performed with aid of the JUROGAM II array. The experiments that used the 148Nd (12C, 4n) 156Dy and 124Sn (36S, 4n) reactions were both conducted using the GAMMASPHERE array. In total, the current work reports the observation of about 30 bands in 156Dy. The spins and parities for the majority of new rotational structures have been successfully assigned using the Directional Correlation from Oriented States (DCO ratios) and polarization anisotropy (Ap). In order to meaningfully describe the quantum behavior of the newly established structures, the Nilsson and Cranked Shell Models have been used. The results also test the latest and most sophisticated quantum theories of nuclear structure and also point to inadequacies of these models, where they exist. Amongst important spectroscopic features, is the identification of the γ wobbling candidate, which implies in some way that 156Dy is γ deformed. Extensions have been made on the γ bands and they are now observed to spins 31+ and 32+, which marks the highest spin to be ever observed for both the odd and even spin members of the γ bands in any nucleus. The current study also reports the first candidate for the aligned γ bands based on the two-quasiparticle configurations (S-band). This is the first time "γ bands" have been identified on both the ground state band (continuation) and on the yrast aligned S-band. Finally, an odd spin negative parity sequence, namely band 9, has been identified as a candidate of the K = 1- octupole excitation. [Please note: the full text of the thesis is deferred until January 2018]